Symmetric Galerkin boundary element method in elastodynamic analysis - Yuan, Weifeng. (2008)
The present research aims to implement the Symmetric Galerkin Boundary Element Method (SGBEM) for 2-dimensional elastodynamic problems. The SGBEM employs both the displacement integral equation and the traction integral equation which lead to a matrix equation with completely symmetric coefficients. This research focuses the effective techniques in dealing with the strong and hypersingular integrals embedded in the SGBEM formulations. To achieve this goal, two versions of the SGBEM implementation are developed where different formulations are derived and various new schemes are proposed.